Penerapan Komunikasi Terapeutik Pada Lansia Di Kelurahan Sendangguwo - Dian Nur Kumalasari; Achmad Syaifudin; Komsiyah Komsiyah; Ayu Dita Handayaningtyas; Fhandy Aldy Mandaty; Sumarno Sumarno (Compromise Journal Community Proffesional Service Journal, 2024)
Communication is the way individuals connect ideas, knowledge and feelings to other people. Communication is focused not only on content but also on individual feelings and emotions. Therapeutics itself is related to therapy, which is an effort to restore the health of someone who is sick, treating illness and treating disease. Meanwhile, therapeutic communication is the sending of messages between the sender and recipient with interaction between the two which aims to restore the health of someone who is sick. Elderly individuals must continue to communicate with other people. Elderly people do not need to withdraw from all activities including communicating. This therapeutic communication is the basis of caring. Where this concern is a characteristic of the nursing profession as a health worker. As an effort to improve the health of the elderly, it is necessary to continuously provide information to the elderly, both individuals and groups, so that the elderly change from not knowing to knowing so that the elderly can live healthy and productive lives, however, with the limitations of the elderly both physically, psychologically and mentally, it is necessary approaches and methods so that the message conveyed is more effective. The approach taken to the elderly is in providing information through therapeutic communication about improving health.